Rising star - Chapman, Linda; Kronheimer, Ann, illus (London : Puffin, 2006)
Currant, the new foal at Orchard Stables, discovers that being a unicorn is not as easy as it seems, particularly when it comes to flying. Luckily, Lauren and Twilight are able to lend a hand, but how can they help Currant overcome his fears?
Keywords: Fiction